(untitled) (Journal on Excellence in College Teaching, 2024)
The effectiveness of embedding commercial video games into higher education humanities classrooms for the purpose of improving undergraduate students’ analytical skills was examined through a single game case study. This collaborative study utilized the PlayStation game Doki Doki UniverseTM to address methods of game implementation, logistic use, and achievement of student learning outcomes. Student journal entries were assessed using qualitative analysis techniques. Examples of student journal entries are provided.